2018
DOI: 10.1016/j.neuroimage.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Generative adversarial networks for reconstructing natural images from brain activity

Abstract: We explore a method for reconstructing visual stimuli from brain activity. Using large databases of natural images we trained a deep convolutional generative adversarial network capable of generating gray scale photos, similar to stimuli presented during two functional magnetic resonance imaging experiments. Using a linear model we learned to predict the generative model's latent space from measured brain activity. The objective was to create an image similar to the presented stimulus image through the previou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 28 publications
0
79
0
Order By: Relevance
“…Earlier studies on decoding stimuli in pixel space either searched for a match in the exemplar set (Naselaris et al, 2009; Nishimoto et al, 2011) or tried to reconstruct the stimulus (Miyawaki et al, 2008; Wen et al, 2016; Güçlütürk et al, 2017; Han et al, 2017; Seeliger et al, 2018; Shen et al, 2019). In the exemplar matching methods, visualization is limited to the samples in the exemplar set and hence these methods cannot be generalized to stimuli that are not included in the exemplar set.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies on decoding stimuli in pixel space either searched for a match in the exemplar set (Naselaris et al, 2009; Nishimoto et al, 2011) or tried to reconstruct the stimulus (Miyawaki et al, 2008; Wen et al, 2016; Güçlütürk et al, 2017; Han et al, 2017; Seeliger et al, 2018; Shen et al, 2019). In the exemplar matching methods, visualization is limited to the samples in the exemplar set and hence these methods cannot be generalized to stimuli that are not included in the exemplar set.…”
Section: Discussionmentioning
confidence: 99%
“…DNN-based reconstruction methods have typically avoided directly training a DNN model for reconstruction (Güçlütürk et al, 2017; Han et al, 2017; Seeliger et al, 2018; Shen et al, 2019). Instead, they have used decoded features as a proxy for hierarchical visual representations encoded in the fMRI activity that was used as the input to a reconstruction module.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An impressive but foreboding body of research has demonstrated the capability of statistical modelling and machine learning techniques to reconstruct images viewed by a participant undergoing an fMRI scan. [162][163][164][165][166][167] For example, a 2019 study by Shen et al 162 demonstrated a generative adversarial network (GAN) model which produced the images in Figure 2.5. The practical relevance of these findings from a security perspective is lacking, given that fMRIs are currently not very suitable for BCI applications due to their size and cost, and the reproduced images The aim was to build a system to believably emulate the user experience of passthought authentication, rather than to build a fully-functional and properly secure authenticator.…”
Section: Diep and Wolbringmentioning
confidence: 99%